ANALISIS REAKSI PASAR TERHADAP SAHAM BLUE CHIP DAN NON-BLUE CHIP YANG MENGALAMI STOCK SPLIT - Handayani, Nadila Dwi; Hascaryani, Tyas Danarti (Contemporary Studies in Economic, Finance and Banking, 2024)
A stock split corporate action usually provokes a market reaction. You can see reactions through volume activity and abnormal returns. This quantitative study aims to examine the market reaction to Blue Chips and non-Blue Chips splitting between 2013 and 2022. The population used consisted of 86 strains consisting of 12 elite and 74 non-elite strains. These shares are listed on the Indonesia Stock Exchange. The survey data is secondary data consisting of the average trading volume before and after the stock split and the average abnormal return before and after the stock split. The methods used are the Wilcoxon Signed Rank Test with normality test and significance level a = 5%. The results of the study explain that there was no significant difference in Trading Volume Activity before and after the stock split for both Blue Chips and non-Blue Chips. On the other hand, when there was no abnormal return, a significant difference was seen for blue-chip stocks, but a significant difference was seen for non-blue-chip stocks before and after the stock split.